Endotoxin Triggers Tumor Initiation Events in Nontumorigenic Breast Epithelial Cells and Enhances Invasion-Related Phenotype in Pretumorigenic and Tumorigenic Breast Epithelial Cells - Farah Yassine; Sabreen F. Fostok; Nataly Naser Al Deen; Rabih S. Talhouk (Hindawi Limited, 2021)
Inflammation is associated with the development of several cancers, including breast cancer. However, the molecular mechanisms driving breast cancer initiation or enhancement by inflammation are yet to be deciphered. Hence, we opted to investigate the role of inflammation in initiating and enhancing tumor-like phenotypes in nontumorigenic, pretumorigenic, and tumorigenic breast epithelial cells. Noncytotoxic endotoxin (ET) concentrations capable of inducing an inflammatory phenotype were determined for the different cell lines. Results showed that short-term ET exposure upregulated matrix metalloproteinase-9 (MMP-9) activity in nontumorigenic mammary epithelial cells of mouse (SCp2) and human origins (HMT-3522 S1; S1) and upregulated inflammatory mediators including nitric oxide (NO) and interleukin 1-β in tumorigenic human breast cells (MDA-MB-231), all in a dose-dependent manner. Long-term ET treatment, but not short-term, triggered the migration of SCp2 cells, and proliferation and migration of tumorigenic human breast cells MCF-7 and MDA-MB-231. Both short- and long-term ET exposures preferentially enhanced the invasion of pretumorigenic S1-connexin 43 knockout (Cx43-KO S1) cells compared to their nontumorigenic S1 counterparts. Moreover, both ET exposures disrupted lumen formation and apicolateral distribution of β-catenin in 3D cultures of S1 cells. In conclusion, ET treatment at concentrations that elicited inflammatory phenotype triggered tumor initiation events in nontumorigenic and pretumorigenic breast cells, and increased tumorigenicity of breast cancer cells. Our findings highlight the role of inflammation in enhancing migration, invasion, and loss of normal 3D morphology and suggest that such inflammatory insults can "add injury" to pretumorigenic and tumorigenic breast epithelial cells.